01 ANALISIS SALURAN DAN MARJIN PEMASARAN UMBI PORANG DI KELURAHAN BALLEANGIN DI KECAMATAN BALOCCI KABUPATEN PANGKAJENE DAN KEPULAUAN - Jurnal Agribis; Muhammad Ibnu Iqbal; Mohammad Anwar Sadat; Azisah Azisah (Universitas Muslim Maros, 2020)
The marketing aspect is very important in marketing agricultural products. If the marketing mechanism is good, then all parties involved will benefit. A farm with good productivity will fail if the marketing is not good. Marketing channels have an important role in the life of farmers. The porang plant is one of the plants that has long been known by the community since ancient times. Until now, porang cultivation has not been widely practiced by the people of Indonesia. This plant now has promising prospects because it has a cultivable economic value. The purpose of this study was to analyze the marketing channels of porang tubers in Balleangin Village, Balocci District, Pangkajene Regency and the Islands, and to analyze the marketing margins of porang tubers in Balleangin Village, Balocci District, Pangkajene Regency and the Islands. This research was conducted in Balleangin Village, Balocci District, Pangkajene Regency and Islands for two months, April - May 2020. Types and sources of data used in this study were primary and secondary data. The data collection techniques used were observation and interviews. The population of this study were all farmers who cultivated porang plants and traders. The sample of farmers was taken as many as 13 people with the simple random sampling method. Traders consist of 4 middlemen and 2 large collectors taken intentionally (purposive). The analysis used was descriptive qualitative and quantitative data analysis. The results showed that there were two marketing channels for porang tubers in Balleangin Village, Balocci District, Pangkajene Regency and the Islands, namely: (1) Channel I: Farmers ? Middlemen ? Large Collectors ? Industry / Consumers, and (2) Channel II: Farmers ? Large Collectors ? Industry / Consumer. The marketing margin for porang tubers in Balleangin Village, Balocci District, Pangkajene Regency and the Islands is Rp. 2,500.